2017
DOI: 10.1016/j.biopsych.2017.02.1176
|View full text |Cite
|
Sign up to set email alerts
|

A Circadian Genomic Signature Common to Ketamine and Sleep Deprivation in the Anterior Cingulate Cortex

Abstract: BACKGROUND Conventional antidepressants usually require several weeks to achieve a full clinical response in patients with major depressive disorder, an illness associated with dysregulated circadian rhythms and a high incidence of suicidality. Two rapid-acting antidepressant strategies, low-dose ketamine (KT) and sleep deprivation (SD) therapies, dramatically reduce depressive symptoms within 24 hours in a subset of major depressive disorder patients. However, it is unknown whether they exert their actions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 81 publications
2
67
0
Order By: Relevance
“…Ketamine treatment led to a rapid and significant reduction in immobility compared with the control saline treatment (Orozco‐Solis et al, ), consistent with the findings of several previous studies (Autry et al, ; Hines, Schmitt, Hines, Moss, & Haydon, ; Lopez‐Rodriguez, Kim, & Poland, ; Scheuing, Chiu, Liao, & Chuang, ). Further comparative transcriptomics analyses revealed that several key rhythmic genes (e.g., Ciart, Per2, Npas4, Dbp, and Rorb) were differentially expressed in the brain in response to ketamine treatment in mice (Orozco‐Solis et al, ). Several studies have demonstrated that ketamine enhanced rapid eye movement (REM) sleep and significantly increased levels of brain‐derived neurotrophic factor (BDNF), a synaptic protein correlated strongly with slow‐wave activity (SWA), to improve BDNF‐mediated synaptic plasticity and depressive symptoms (Ballard et al, ; Duncan et al, ; Evans et al, ; Monteggia & Zarate, ; Zarate & Machado‐Vieira, ).…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…Ketamine treatment led to a rapid and significant reduction in immobility compared with the control saline treatment (Orozco‐Solis et al, ), consistent with the findings of several previous studies (Autry et al, ; Hines, Schmitt, Hines, Moss, & Haydon, ; Lopez‐Rodriguez, Kim, & Poland, ; Scheuing, Chiu, Liao, & Chuang, ). Further comparative transcriptomics analyses revealed that several key rhythmic genes (e.g., Ciart, Per2, Npas4, Dbp, and Rorb) were differentially expressed in the brain in response to ketamine treatment in mice (Orozco‐Solis et al, ). Several studies have demonstrated that ketamine enhanced rapid eye movement (REM) sleep and significantly increased levels of brain‐derived neurotrophic factor (BDNF), a synaptic protein correlated strongly with slow‐wave activity (SWA), to improve BDNF‐mediated synaptic plasticity and depressive symptoms (Ballard et al, ; Duncan et al, ; Evans et al, ; Monteggia & Zarate, ; Zarate & Machado‐Vieira, ).…”
Section: Introductionsupporting
confidence: 87%
“…Interestingly, some studies also have shown that circadian rhythms return to normal as depression symptoms remit (Avery, Shah, Eder, & Wildschiodtz, 1999;Hasler, Buysse, Kupfer, & Germain, 2010;Souetre et al, 1988;Troxel et al, 2012). A recent study from the University of California at Irvine involved transcriptome profiling to identify genes and pathways in relation to ketamine-associated alterations in circadian and sleep rhythms in mice (Orozco-Solis et al, 2017).…”
Section: Ketamine Improves Disrupted Circadian and Sleep Rhythmsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to the time required to normalize the whole-body circadian rhythm, which is the reason why antidepressants have a delayed therapeutic response. Recently, three antidepressant modalities have become the focus of research because of their very rapid antidepressant effect: sleep deprivation, electroconvulsive therapy, and ketamine therapy [19][20][21]. Previous evidence suggests that the mechanism underlying the antidepressant effect is a process in which the delayed circadian rhythm is restored to normal by treatment [22].…”
Section: Circadian Misalignment In Bipolar Disordermentioning
confidence: 99%